Utilização de blend de enzimas e levedura na alimentação de bovinos leiteiros - Dessbesell, Jéssica Gabi (2020)
The objective of this assignment was to evaluate the use of enzyme blends and yeast blends in the feeding of dairy cattle. We used nine Holstein cows with 84.77 (± 21.25) days of lactation, body weight of 616.22 (± 60.64) kg and initial production of 30.44 (± 3.16) kg of milk daily. The parameters of intake and digestibility of dry matter (DM) and nutrients, microbial synthesis, blood metabolites and milk production and composition were analyzed. In addition to lactating cows, six male castrated bovines of the Jersey breed, with ruminal cannula (780.83 ± 44.16 kg), with approximately nine years of age, were used. We analyzed the parameters of intake and digestibility of dry matter and nutrients, ruminal parameters and cumulative gas production in vitro. Distributed in double 3x3 Latin square, the experiment lasted 63 days. The diet consisted of 50% corn silage and 50% concentrated, which was divided into three treatments: 1) control; 2) enzymes blend; 3) yeast blend. For lactating cows, the use of enzyme blend and yeast blend did not change the intake of DM and other nutrients, such as the digestibility of DM and nutrients, there was a significant difference (p> 0.05) between treatments for milk urea nitrogen, the diet with the inclusion of the yeast blend had a higher concentration (17.75 mg / dL) and the cows fed with the inclusion of enzyme blend showed lower concentration (15.18 mg / dL). Milk production was higher for the animals that received the diet with the addition of the yeast blend, such as blood urea concentrations. In the experiment with cannulated cattle there was no effect of treatments (p> 0.05) for cumulative production of gas in vitro, as well as for ammoniacal nitrogen concentrations (N-NH3), obtaining the maximum point (37.08 mg dL-1) 2:00 hours after morning feeding and the minimum point (14.66 mg dL-1) 8:00 hours after morning feeding. Thus, the addition of 200 g of enzyme blend and 2 kg of yeast blend per ton of concentrated ration, in the feed of cannulated cattle does not change the intake and digestibility of DM and nutrients and rumen fermentation parameters. For cows, the use of yeast blend increased milk production, as well as blood and milk urea nitrogen.